2014
DOI: 10.1161/jaha.114.000963
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Door‐to‐Puncture Times for Intra‐Arterial Stroke Therapy: A Pilot Quality Improvement Project

Abstract: BackgroundDelays to intra‐arterial therapy (IAT) lead to worse outcomes in stroke patients with proximal occlusions. Little is known regarding the magnitude of, and reasons for, these delays. In a pilot quality improvement (QI) project, we sought to examine and improve our door‐puncture times.Methods and ResultsFor anterior‐circulation stroke patients who underwent IAT, we retrospectively calculated in‐hospital time delays associated with various phases from patient arrival to groin puncture. We formulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 30 publications
2
76
2
2
Order By: Relevance
“…Also, as is wellknown, any delay in the time before reperfusion can lead to worse outcomes, and the prognosis improves the sooner endovascular reperfusion is achieved. [24][25][26] Hence, choosing a small stent with excellent deliverability could achieve quicker lesion location and thus avoid wasting time. Selection bias of stent choice exists in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as is wellknown, any delay in the time before reperfusion can lead to worse outcomes, and the prognosis improves the sooner endovascular reperfusion is achieved. [24][25][26] Hence, choosing a small stent with excellent deliverability could achieve quicker lesion location and thus avoid wasting time. Selection bias of stent choice exists in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…The median door-to-first angiography series time of 102 min achieved by the stroke room intervention was shorter than the time taken for start of treatment reported in most of the earlier studies [13,14,23,24] . However, the Eurostroke registry, which contains data from 12 stroke centers in Germany and Austria, reports median door-tofirst angiography series times of 91 min for patients with anterior circulation ischemia and of 99 min for patients with vertebrobasilar ischemia [20] .…”
Section: Discussionmentioning
confidence: 62%
“…Recently, the results of an interventional study aimed at reducing the delays before IAT were reported [23] . This intervention, based on a protocol for early alert of the neurointerventional radiology team about arriving patients with suspicion of stroke even before image acquisition and a consequent parallel work flow, allowed the researchers to reduce median door-to-groin puncture times from 143 to 107 min.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the stroke workflow needs to run in a parallel fashion rather than being a linear process. 53,54 IV-tPA could be administered in the imaging suite as soon as the NCCT excludes hemorrhage, while CTA/CTP imaging is simultaneously being performed. 55 The stroke imaging protocols need to be modeled after trauma, necessitating the same level of urgency, targeting all points of delay: stroke-alert notification to radiologists, point-of-care testing, forgo blood work to verify creatinine levels, separation of reads of NCCT from multimodal imaging (CTA/CTP), rapid automated postprocessing of perfusion when performed, and convergence of teams to CT/MR imaging, where management decisions are made.…”
Section: Quality and Safety In Stroke Imagingmentioning
confidence: 99%